(untitled) (European Journal of Education and Psychology, 2010)
We present a descriptive research study with crossover design, the overall aim was to study the beliefs and strategies used by students for weight control, satisfaction / dissatisfaction with their body image and relations with self-esteem. The sample consisted of 740 students at the University of Almeria, selected by a stratified sampling procedure by gender, course and facility, which completed the Questionnaire of Beliefs and Strategies for Weight Management, developed ad hoc for this research, and Rosenberg Self-Esteem Questionnaire. The overall results show that 73.7% of the total sample does not use strategies to control weight, and only 48.2% of the total sample, they try to control it. The highest percentage of women identified with the actual physical prototype and the prototype fleshy most desired is the Athletic. The largest percentage of men are identified in the current prototype this prototype is athletic and the most desired. The 48.16% of the subjects are satisfied with their current prototype and the 51.84% shown is unsatisfied. Men are significantly more satisfied with their body image than women and more satisfied subjects have higher self-esteem.